2006
DOI: 10.1111/j.1745-7254.2006.00459.x
|View full text |Cite|
|
Sign up to set email alerts
|

Antisense oligonucleotides targeting midkine induced apoptosis and increased chemosensitivity in hepatocellular carcinoma cells

Abstract: Aim: Overexpression of midkine (MK) has been observed in many malignancies. This aim of this study is to screen for suitable antisense oligonucleotides (ASODN) targeting MK in hepatocellular carcinoma (HCC) cells and evaluate its antitumor activity. Methods: Ten ASODN targeting MK were designed and synthesized. After transfection with ASODN, cell proliferation was analyzed with MTS [3 ‐(4,5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H‐tetrazolium, inner salt] assay. In addition, MK mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Additionally, MK, an angiogenic factor, is expressed in bladder cancer, www.wjgnet.com and its over-expression correlates with a poor outcome in patients with invasive cancers [20] . In fact, we have confirmed that MK-AS transfer can significantly inhibit the growth of hepatocellular carcinoma cells, which is associated with increased Caspase-3 activity [34] . The present study was to determine whether MK-AS can suppress angiogenesis, which is an important mechanism underlying inhibition of tumor cell proliferation.…”
Section: Introductionsupporting
confidence: 63%
“…Additionally, MK, an angiogenic factor, is expressed in bladder cancer, www.wjgnet.com and its over-expression correlates with a poor outcome in patients with invasive cancers [20] . In fact, we have confirmed that MK-AS transfer can significantly inhibit the growth of hepatocellular carcinoma cells, which is associated with increased Caspase-3 activity [34] . The present study was to determine whether MK-AS can suppress angiogenesis, which is an important mechanism underlying inhibition of tumor cell proliferation.…”
Section: Introductionsupporting
confidence: 63%
“…In fact, several studies have been reported that antisense targeting MK inhibits tumor growth, such as human prostate cells, colon carcinoma cells [26] , and mouse rectal carcinoma cells [27] . We previously confirmed that MK-AS could significantly inhibit growth of hepatocellular cells including HepG2, SMMC-7721, and BEL-7402 [28] . The aim of this study was to evaluate the in vivo antitumor effects of MK-AS in an in situ human hepatocellular carcinoma model in mice.…”
Section: Introductionmentioning
confidence: 74%
“…Recently, HCC tumor cells were found to overexpress MK. In our previous studies, ASODNs that target MK were demonstrated to play an important role in anti-tumor functions [15,16] . However, the anti-tumor effect was not satisfactory and found to be toxic because of the absence of smart and safer delivery tools.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study [15] , this antisense sequence has been identified to be the most effective sequence for the down-regulation of MK. Consequently, this sequence was synthesized and applied in this study.…”
Section: Asodn Synthesismentioning
confidence: 98%